Promoting, seeking, and reaching vaccination services: A systematic review of costs to immunization programs, beneficiaries, and caregivers. Issue 32 (22nd July 2021) - Yemeke, Tatenda T.; Mitgang, Elizabeth; Wedlock, Patrick T.; Higgins, Colleen; Chen, Hui-Han; Pallas, Sarah W.; Abimbola, Taiwo; Wallace, Aaron; Bartsch, Sarah M.; Lee, Bruce Y; Ozawa, Sachiko
Highlights: First systematic analyses to document costs for beneficiaries seeking vaccination. Reviewed evidence on costs for beneficiaries to seek and reach vaccination sites. Limited evidence available for costs incurred by beneficiaries to seek vaccination. Higher costs for beneficiaries facing hard-to-reach barriers to vaccination. Costs from beneficiary perspective may be a barrier to people getting vaccinated. Abstract: Introduction: Understanding the costs to increase vaccination demand among under-vaccinated populations, as well as costs incurred by beneficiaries and caregivers for reaching vaccination sites, is essential to improving vaccination coverage. However, there have not been systematic analyses documenting such costs for beneficiaries and caregivers seeking vaccination. Methods: We searched PubMed, Scopus, and the Immunization Delivery Cost Catalogue (IDCC) in 2019 for the costs for beneficiaries and caregivers to 1) seek and know how to access vaccination (i.e., costs to immunization programs for social mobilization and interventions to increase vaccination demand), 2) take time off from work, chores, or school for vaccination (i.e., productivity costs), and 3) travel to vaccination sites. We assessed if these costs were specific to populations that faced other non-cost barriers, based on a framework for defining hard-to-reach and hard-to-vaccinate populations for vaccination. Results: We found 57 studies describing information, education, and communication (IEC) costs, social mobilization costs, and the costs of interventions to increase vaccination demand, with mean costs per dose at $0.41 (standard deviation (SD) $0.83), $18.86 (SD $50.65) and $28.23 (SD $76.09) in low-, middle-, and high-income countries, respectively. Five studies described productivity losses incurred by beneficiaries and caregivers seeking vaccination ($38.33 per person; SD $14.72; n = 3). We identified six studies on travel costs incurred by beneficiaries and caregivers attending vaccination sites ($11.25 per person; SD $9.54; n = 4). Two studies reported social mobilization costs per dose specific to hard-to-reach populations, which were 2–3.5 times higher than costs for the general population. Eight studies described barriers to vaccination among hard-to-reach populations. Conclusion: Social mobilization/IEC costs are well-characterized, but evidence is limited on costs incurred by beneficiaries and caregivers getting to vaccination sites. Understanding the potential incremental costs for populations facing barriers to reach vaccination sites is essential to improving vaccine program financing and planning.